Classic ataxia-telangiectasia: the phenotype of long-term survivors - van Os, Nienke J. H. (J Neurol, 2019)
OBJECTIVE: Patients with classic ataxia–telangiectasia (A–T) generally die in the second or third decade of life. Clinical descriptions of A–T tend to focus on the symptoms at presentation. However, during the course of the disease, other symptoms and complications emerge. As long-term survivors with classic A–T develop a complex multisystem disorder with a largely unknown extent and severity, we aimed to comprehensively assess their full clinical picture. METHODS: Data from Dutch patients with classic A–T above the age of 30 years were retrospectively collected. In addition, we searched the literature for descriptions of classic A–T patients who survived beyond the age of 30 years. RESULTS: In the Dutch cohort, seven classic A–T patients survived beyond 30 years of age. Fourteen additional patients were retrieved by the literature search. Common problems in older patients with classic A–T were linked to ageing. Most patients had pulmonary, endocrine, cardiovascular, and gastro-intestinal problems. All patients had a tetraparesis with contractures. This led to immobilization and frequent hospital admissions. Most patients expressed the wish to no longer undergo intensive medical treatments, and waived follow-up programs. CONCLUSIONS: Paucity of descriptions in the literature, and withdrawal from medical care complicate the acquisition of follow-up data on the natural history of long-term survivors. Irrespective of these limitations, we have obtained impression of the many problems that these patients face when surviving beyond 30 years of age. Awareness of these problems is needed to guide follow-up, counselling, and (palliative) care; decisions about life-prolonging treatments should be well considered. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00415-019-09641-1) contains supplementary material, which is available to authorized users.